Problem Posing of High School Mathematics Student's Based on Their Cognitive Style - Abdul Rahman; Ansari Saleh Ahmar (ÜNİVERSİTEPARK Limited, 2017)
Mathematical problem posing plays an important role in mathematics curriculum, since it encompasses the core of mathematics activities, among other things, with students' activities to construct their own problems as the preliminary step to actual problem solving steps. This study aims at revealing the profile of students' mathematical problem posing based on their cognitive styles in order to know and understand the learning of mathematics students. As a result of this study, students who have the cognitive style 'field independent' (FI) are able to propose a solvable mathematical problem and load new data, and also pose problems categorized as high-quality mathematical problems. Students who have the cognitive style of 'field dependent' (FD) are generally limited to solvable mathematical problems that do not contain new data, and mathematical problems of a moderate level. In this study, it is seen how student's work mathematical problem posing using their cognitive style, resulting in a breakthrough in the process of learning to use students' cognitive styles so as to increase the quality of learning outcomes.